Effects of chronic cortisol administration on global expression of GR and the liver transcriptome in Sparus aurata - Teles, Mariana (2018)
The present work was designed to assess the effects of artificially increased high plasma cortisol levels induced by slow-release cortisol implants on the mRNA abundance of the glucocorticoid receptor (GR) in different organs of Sparus aurata (Gilthead sea bream), as well as to evaluate global transcriptional changes in the liver, using the Aquagenomics S. aurata oligo-nucleotide microarray technology. For that purpose, groups of fish were intraperitoneally injected with implants containing two different concentrations of cortisol (50 or 200 μg/g body weight). Blood and organs were sampled after 7 and 14 days of cortisol implantation. Only fish with 200 μg/g implants exhibited a significant rise in plasma cortisol. Thus, we evaluated the expression of the GR in different organs in these fish 7 and 14 days post-implantation. GR mRNA abundance was upregulated in head kidney and heart of fish at both sampling times. In liver and muscle, GR mRNA abundance was upregulated after 14 days, whereas in gills, the GR mRNA transcript was upregulated earlier, at day 7. These results suggest that increased plasma cortisol induced by a slow-release implant of cortisol mimics the overall effects of stress and affects the expression of GR mRNA in a time- and organ-specific manner. Data obtained with the Aquagenomics S. aurata oligo-nucleotide microarray allowed the identification of a total of 491 cortisol-responsive transcripts and highlight the strong intensity of transcriptional modulation in liver of fish implanted with cortisol after 7 days, in contrast to that observed at day 14. Transcriptional remodeling highlighted a significant activity in carbohydrate metabolism mainly in the gluconeogenic pathway linked to downregulation of inflammatory and immune response processes in implanted fish.